Strategy of TVRI Jawa Barat Film Festival Program in Increasing the Participation of Young Cineast in West Java - Widjajanto, Kenmada; Praratya, Atalia; Dwiwaloejo, Soerachman; Pradana, Rizky Satrio (Green Publisher Indonesia, 2025)
Audio visual media is a medium that is very popular with today's young generation. Technological advances have supported the creation of audio-visual works, especially films, both low-cost and high-cost. Social media such as YouTube, Instagram, Tiktok and Facebook are free platforms that are widely used to promote their creative works to audiences all over the world. This encouraged TVRI Jawa Barat to hold a Short Film Festival as a means of appreciating creative works of art for the younger generation who are interested in the field of filmmaking. The objective is to select and award the best film creators and collaborate with TVRI Jawa Barat, create media for promoting film works to audiences and producers and provide a platform for young filmmakers to share knowledge, experience and skills related to film production. TVRI Jawa Barat's involvement in advancing film in West Java is an interesting research object. This research was carried out to find out what strategies were designed by the TVRI Jawa Barat Film Festival Program in order to gain the participation of young filmmakers in West Java. This research, which uses qualitative methods with a case study approach through a series of observation activities, in-depth interviews and document studies, shows several interesting results, including an increase in the number of participants in the third event by 1000% with a strategy of determining free themes and genres but still referring to normative standards Indonesian Broadcasting Commission (KPI)